Audit on the Management of Bronchiolitis: A Single Centre Real World Experience in Bangladesh Can We do Better ? - Hamid, Farzana; Quaium, Syed Moosa MA; Rahman, Azizur; Ahmad, AT Reza; Khan, Shahariar; Hussain, Tania; Zahra, Fatematuz (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Background: Bronchiolitis is the most common reason for hospitalization of children in many countries.Though Respiratory Syncytial Virus (RSV) is the most common organism causing bronchiolitis, but antibiotics are used widely.So the aim of the present study is to establish whether antibiotic has any role in bronchiolitis management along with supportive treatment. Methods:This retrospective study included 100 infants and children between 2-24 months of age admitted with clear cut sign symptoms of bronchiolitis. Patients were divided into Group A (supportive + antibiotic Rx) comprised 72 patients and group B (supportive Rx only) comprised 28 patients.After 3-5 days of hospital stay, clinical responses were evaluated in terms of improvement in symptoms and clinical parameters- respiratory rate, heart rate and oxygen saturation. Results: Mean age of patients was 6.6 (±5.6) months in Group A and 6.3 (±4.8) months in Group B. Most of the patients in both study groups were male (M: F=1.6:1). All the cases in both groups presented with cough, running nose, and respiratory distress. Fever and feeding difficulty were present in 83.3% & 90.3% in Group A and 82.1% & 89.3% in Group B respectively. Majority of cases were from lower socioeconomic status and lived in urban area. In Group A, after therapy mean respiratory rate 53.7 (±4.3) and oxygen saturation 97.9 (±1.9) had significantly improved in comparison to respiratory rate 65.6 (±4.8) and oxygen saturation 89.7 (±4.4) before therapy (p=<.001 in all parameter). Heart rate also significantly increased after therapy (149.4 ±10.2 versus 104.5 ±8.7) (p=<.001). In Group B, after therapy mean respiratory rate 53.5 (±4.1) and oxygen saturation 97.8 (±1.7) had also significantly improved in comparison to respiratory rate 65.3 (±4.1) and oxygen saturation 88.8 (±2.8) before therapy (p=<.001 in all parameter). Heart rate also significantly increased after therapy (150.8 ±9.8 versus 105.0 ±6.2) (p=<.001). In comparison between two modalities of treatment, no significant difference was found (p value=>.05 in all parameters). No statistical significant difference was observed in the length of hospital stay in two groups. Conclusion: The study highlighted the importance of supportive treatment in bronchiolitis management. Antibiotics should not be used without clinical and laboratory evidence of bacterial infection. DOI: http://dx.doi.org/10.3329/cmoshmcj.v14i1.22871 Chatt Maa Shi Hosp Med Coll J; Vol.14 (1); Jan 2015; Page 6-10